Investigating the effectiveness of iPad based language learning in the UAE context. (3rd April 2022) - Grigoryan, Tsoghik
ABSTRACT: This mixed-methods true experimental study aimed at exploring the results of using mobile technology educationally by looking into learner practices and attitudes towards using iPads in language learning, as well as looking into students' language achievement as developed by the paperless classroom. Four research questions guided this study. The quantitative analyses were obtained through the test scores and survey questionnaires. The qualitative analyses were obtained through teachers' weekly reflective journals. This study conducted an Activity Theory based enquiry into iPad implementation for language learning in terms of student motivation, satisfaction, device usefulness and learning effectiveness, and conceptualised a research model to provide insights into learner perceptions of the iPads in an educational setting, which was then analysed through factor analysis. The experimental results revealed that level one language learners progress in learning English better when using iPads as compared to using textbooks. The experimental phase results were well supported by the results of the survey analyses, which showed a positive relationship between students' attitudes towards iPad implementation as a means of language learning and their language achievement.